Fin whale acoustic populations present in New Zealand waters: Description of song types, occurrence and seasonality using passive acoustic monitoring. - Alexandra N Constaratas (Public Library of Science (PLoS), 2021)
Southern fin whales (Balaenoptera physalus) are known to migrate from the Antarctic to mid-latitudes during winter for breeding, but the occurrence and distribution of this species is not well known in the waters around New Zealand. The 'doublet' calls are one of the main calls emitted specifically by fin whales and repeated in a regular pattern, which make the acoustic detection of these calls relevant to detect the presence of fin whales. Using a signal processing algorithm to detect 'doublet' calls emitted by fin whales, we studied the occurrence, characteristics and seasonality of these 'doublet' calls in two regions around New Zealand; Cook Strait in 2016/2017 and offshore Gisborne in 2014/2015. The call detection procedure consisted of binarization of the spectrogram and a cross-correlation between the binarized spectrogram and a template of binarized 'doublet' calls spectrogram. A binarization threshold for the data spectrograms and a cross correlation threshold were then determined through multiple trials on a training dataset and a Receiver Operating Characteristics (ROC) curve. Fin whale 'doublet' calls occurred on the east side of New Zealand's Cook Strait during austral winter, specifically in June 2017 and offshore Gisborne in June-August 2014. No 'doublet' calls were detected on the west side of Cook Strait. The 'doublet' calls' Inter-Note Interval (INI) was similar in both datasets. However, there was a difference in alternation of the mean frequency for both HF components of 'doublet' calls in Cook Strait and Gisborne. As the song types were compared with those previously described in the literature, our findings suggest that some fin whales wintering in New Zealand waters may be part of a broader 'acoustic population' whose range extends west to southern Australia and south to Antarctica.